Structural and Dielectric Properties of Bi-Zn Substituted Calcium Copper Titanate (CCTO). (May 2020) - Kumar, Vikas; Mohammed, J.; Tchouank Tekou, Carol T.; Mukhtar, G.; Halilu, N.; Adamu, I. A.; Maji, Pradip. K.; Basandrai, Deepak.; Srivastava, A. K.
Abstract: Calcium copper titanate (CCTO), an electroceramic with giant dielectric constant is useful in supercapacitor, microwave absorption, shielding of electromagnetic interference, and high frequency application. Bi 3+ -Zn 2+ substituted CCTO with chemical composition Ca1-x Bix Cu3 Ti4-x Znx O12 (0.0<x<0.2) was fortified using sol-gel auto combustion technique and were characterized using XRD, FESEM, and impedance analyser. XRD confirms the formation of CCTO phase with some traces of CuO and CaTiO3 phase. FESEM micrograph shows particles shapes close to cubic shape.